PERSEPSI REMAJA TENTANG PELAKSANAAN LAYANAN INFORMASI OLEH MAHASISWA PRAKTIK PENGALAMAN LAPANGAN BIMBINGAN DAN KONSELING (PPLBK) TERPADU ANGKATAN TAHUN 2009 DI KELURAHAN AIR PACAH KOTA PADANG - Rahma, Yulia; Ibrahim, Indra; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
Implementation of information services by students practical field experience integrated guidance and counseling to adolescents aims to provide new knowledge and experience in accordance with the needs of the young. In Air Pacah revealed that the implementation of services students practice guidance and counseling field experience integrated rudimentary noted that less enthusiastic in participating in these activities. This study describes: 1. Perceptions of adolescents in urban Air Pacah of materials provided students in the implementation of information services, 2. Perceptions of adolescents in the village Air PacahÂ about the methods used in the implementation of information services, 3. Perceptions of adolescents in the village Air Pacah about media used in the implementation of information services. This type of research is descriptive with a population of 33 teenagers have a population of less than 100 people, the population sample used in this study by using total sampling. Data collection tool is questionnaire data analysis techniques using a percentage formula. Show study findings: 1. Perceptions of young people in villages Air Pacah on the material provided in the implementation of students information service are the less important criterion, 2. Perceptions of young people in villages Air Pacah about the methods used in the implementation of information service on a less suitable criteria, 3. Perceptions of young people inÂ villages Air Pacah of media used in the implementation of information service in the category which not appropriate. Based on the findings of the study are expected to guidance and counseling students which implement to be more selective in the choice of methods and the media to be used in the implementation of management information service and to continue to implement a program of study in order face to face meetings with students to know the developments in the field. Â